Analysis of Community Satisfaction Index (SMI) Towards Public Services of the Dukcapil Department of Seluma District - Lupita Sari; Karona Cahya Susena; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to analyze the Community Satisfaction Index (CSI) on the Public Services of the Dukcapil Department in Seluma Regency. The sample in this study amounted to 181 people who carried out the management of KK and KTP at the Dukcapil Department of Seluma Regency. Data were collected using a questionnaire analyzed by measuring the value of the Community Satisfaction Index (CSI) based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 14 of 2017. The Community Satisfaction Index (CSI) for the quality of service at the Dukcapil Department of Seluma Regency obtained an average value of 3.01 which was in a good assessment, then the CSI of the service unit was multiplied by 25 so that the CSI was 75.25 with a service B with good criteria because it is in the interval value of 62.51 – 81.25. The element of cost/tariff gets the highest rating with an average value of 3.48 with very good assessment criteria. This illustrates that the community considers the Dukcapil Department of Seluma Regency to provide services free of charge without being charged. The lowest satisfaction value is 2.33 with a poor assessment on the elements of facilities and infrastructure, this illustrates that the facilities and infrastructure provided by the department in providing services to the community have not been maximized.